Zombies the truth behind history's terrifying flesh-eaters - Goldsworthy, Steve (Mankato, Minnesota Capstone Press, 2016)
"Describes ancient history, medieval lore, and modern portrayals of zombies in today's popular culture"--
The world of zombies -- Zombies in the ancient world -- Medieval zombie lore -- Hunting the living dead -- Zombies everywhere
The world around us
Includes bibliographical references and index
8-12
Grades 4-6
1 2 13 15
NEW_ZTN_GN
Keywords: Zombies in literature -- Juvenile literature; Zombies -- Juvenile literature; Zombies -- History -- Juvenile literature